SOSIALISASI PENGENALAN APLIKASI STUNTING DAN TUMBUH KEMBANG BALITA PADA DESA CIPUTRI –KABUPATEN CIANJUR - Hakim, Lukman; Santoso, Hadi; Yusuf, Mohamad (Jurnal Pengabdian dan Kewirausahaan, 2025)
Government Policies on Improving Nutritious Eating as a Priority in Combating Stunting The government’s policy to enhance nutritious eating is currently a priority in addressing stunting, as outlined in Presidential Regulation No. 72 of 2021 on Stunting Reduction. Stunting is a growth impairment condition caused by recurrent malnutrition. Ciputri Village, located in Pacet District, Cianjur Regency, with an area of 6.36 hectares and comprising four hamlets, still has a stunting prevalence of 1.03% among toddlers. A community service program involving LLDIKTI 3, in collaboration with the Cianjur Regency and several universities in Jakarta, was conducted. The purpose of the program was to provide understanding and socialization on the impacts and factors contributing to stunting in toddlers, as well as the use of a stunting application for monitoring the growth and development history of toddlers. The community service activities included preparatory observations and implementation on November 13-14, 2024. The program involved the presentation of the stunting and growth monitoring application and explanations of facial recognition for accessing the application. The program was attended by 25 participants, and the results were evaluated through a questionnaire. Based on the questionnaire, the expectation score was 3.52, while the reality score was 3.48 on a scale of 1-4, indicating overall satisfaction with the community service program.